Mulberry leaf extract improves non-specific immunity and antioxidant capacity of largemouth bass (Micropterus salmoides) fed a high-starch diet - Tingsen, Jing; Hui, Luo; Junwa, Huang; Zhe, Li; Yu, Li; Honghao, Jin; Xinxi, Zou; Zhenlin, Ke; Wenbo, Sun; Mengdan, Hou; Huijun, Yang; Hua, Ye (Frontiers in Marine Science, 2022)
A 70-day experiment was conducted to investigate the effects of mulberry leaf extract (MLE) on growth, proximate compositions, antioxidant and plasma biochemical parameters, and indices of non-specific immunity of largemouth bass (Micropterus salmoides) fed a high-starch diet. Two hundred eighty largemouth bass (initial body weight, 68.00 ± 0.19 g) were randomly fed seven diets: basal-starch diet (BSD; 8.88% starch), high-starch diet (HSD; 11.42% starch), and HSD diets supplemented with 0.05%, 0.10%, 0.20%, 0.50%, and 1.00% MLE (MLE1, MLE2, MLE3, MLE4, and MLE5, respectively). The results indicated that HSD and MLE did not significantly affect the growth performance of largemouth bass during the experimental period compared with that of the BSD, but the supplementation with more than 0.20% (MLE3, MLE4, and MLE5) MLE significantly decreased the hepatosomatic index (HSI) values, and 1.00% (MLE5) MLE significantly decreased the viscerosomatic index (VSI) values. The whole-body moisture of fish fed an HSD decreased significantly, while the whole-body lipid content increased significantly in the HSD group compared with the BSD group. Compared with HSD, MLE supplementation significantly decreased the moisture and lipid contents in the whole body. Supplementation with more than 0.20% MLE (MLE3, MLE4, and MLE5) significantly decreased the moisture content in the muscle. Supplementation with 1.00% MLE significantly decreased the content of hepatic and muscle glycogen. The malondialdehyde (MDA) content of the HSD group was significantly increased compared to that of the BSD group, whereas more than 0.10% (MLE2, MLE3, MLE4, and MLE5) MLE significantly decreased the MDA content. Additionally, the total antioxidant capacity (T-AOC), catalase (CAT), and glutathione peroxidase (GSH-Px) activities of MLE5 were significantly higher than those of the HSD group. The complement-3 (C3) content and globulin (GLB) in the plasma of the HSD group were significantly lower than those of the BSD group. Plasma C3 levels in the MLE3, MLE4, and MLE5 groups were significantly higher than those in the HSD group. In addition, glucose (GLU) levels in the MLE3, MLE4, and MLE5 groups were significantly lower than those in the HSD group. Supplementation with 0.50% (MLE4) MLE significantly increased the lysozyme (LYZ) content and decreased the activities of alanine transaminase (ALT) and aspartate transaminase (AST). Supplementation with 1.00% MLE significantly increased complement-4 (C4) and GLB contents and alkaline phosphatase (ALP) activity. Overall, these findings suggest that MLE could improve antioxidant capacity, immune function, and glycolipid metabolism, thereby alleviating the negative effects of a high-starch diet in M. salmoides.